Turnaround de empresas com problemas de compliance - o caso Siemens - Fonseca, Nadine Corrêa Machado (2015)
It is very relevant, for academic or for society purposes as a whole the subject 'corruption', a recurring problem that plagues companies and Governments in various parts of the world. Many recent cases draw attention to this topic, but one in particular, the case of corruption of the company Siemens AG, that resulted in the payment of the largest fines in the history on your model, based on the terms of the FCPA since it became law in 1977. This event caters specifically to the objective of this work which is to make an analysis based on agency theory and the codes of good practices of corporate governance on how large companies revising their corporate management systems and practices aiming at the recovery of its institutional image after significant impact on the company, such as the corruption scandal in which Siemens was involved. For this study, we opted for qualitative research as a methodological path contemplating the single case study. In the process of data collection were used data obtained through documentary research about the corruption scandal on public collection available in the internet. Open conversations were made with 3 compliance Department officials of Siemens for the purposes of understanding the case with. At the end of this work, it was observed in the Siemens turnaround process a correlation between what was proposed by the Agency Theory about internal control Systems based on what was accomplished by the company when promoted an extensive restructuring of the Department of compliance and corporate governance system, the improvement of internal controls, as well as the creation of detection tools , control, analysis and prevention of fraud, which were used to minimize the effects generated by the conflict of interest covered by the theory of Agency. KEY WORDS: Corporate Governance; Compliance; Corruption; Turnaround, Agency Theory